Anterior Forebrain Neurons Develop Selectivity by an Intermediate Stage of Birdsong Learning - Solis, Michele M. (J Neurosci, 1997)
Auditory neurons of the anterior forebrain (AF) in adult zebra finches are highly selective for the bird’s own song (BOS): they respond more to BOS than to songs of other zebra finches (conspecifics) and to BOS played in reverse. In contrast, juvenile AF neurons are not selective at 30 d of age, responding equally well to all song stimuli. Both BOS and tutor song experience are required by juveniles for normal song learning and may produce the selective properties of adult neurons. Because such selectivity could subserve song learning, it is important to determine when it arises. Birds were therefore studied at an intermediate stage of learning, after substantial experience of both tutor song and their own developing (plastic) song. Extracellular single neuron recordings in 60-d-old zebra finches revealed that AF neurons had significant song and order selectivity for both tutor song and BOS (the bird’s plastic song). The degree of BOS selectivity was less than that found in adults, as indicated in part by 60 d neurons that were sensitive to the local order within syllables but not yet to the global order of syllables within a song. When responses to BOS and tutor song were compared, most neurons preferred BOS, some preferred tutor song, and others responded equally to both stimuli. The latter type of neuron was not simply immature, because many of these neurons responded significantly more to BOS and tutor song than to conspecific and reverse songs. The selectivity of AF neurons at 60 d is markedly different from the unselective properties of neurons at 30 d and may function in vocal learning at this stage. Moreover, the selectivity for both BOS and tutor song raises the possibility that both aspects of the birds’ sensory experience during learning are reflected in properties of AF neurons.